Risk assessments for quality-assured, source-segregated composts and anaerobic digestates for a circular bioeconomy in the UK. (June 2019) - Longhurst, Philip J.; Tompkins, David; Pollard, Simon J.T.; Hough, Rupert L.; Chambers, Brian; Gale, Paul; Tyrrel, Sean; Villa, Raffaella; Taylor, Matthew; Wu, Shaomin; Sakrabani, Ruben; Litterick, Audrey; et al.
Abstract: A circular economy relies on demonstrating the quality and environmental safety of wastes that are recovered and reused as products. Policy-level risk assessments, using generalised exposure scenarios, and informed by stakeholder communities have been used to appraise the acceptability of necessary changes to legislation, allowing wastes to be valued, reused and marketed. Through an extensive risk assessment exercise, summarised in this paper, we explore the burden of proof required to offer safety assurance to consumer and brand-sensitive food sectors in light of attempts to declassify, as wastes, quality-assured, source-segregated compost and anaerobic digestate products in the United Kingdom. We report the residual microbiological and chemical risks estimated for both products in land application scenarios and discuss these in the context of an emerging UK bioeconomy worth £52bn per annum. Using plausible worst case assumptions, as demanded by the quality food sector, risk estimates and hazard quotients were estimated to be low or negligible. For example, the human health risk of E. coli 0157 illness from exposure to microbial residuals in quality-assured composts, through a ready-to-eat vegetable consumption exposure route, was estimated at ~10 −8 per person per annum. For anaerobic digestion residues, 7 × 10 −3 cases of E. coli 0157 were estimated per annum, a potential contribution of 0.0007% of total UK cases. Hazard quotients for potential chemical contaminants in both products were insufficient in magnitude to merit detailed quantitative risk assessments. Stakeholder engagement and expert review was also a substantive feature of this study. We conclude that quality-assured, source-segregated products applied to land, under UK quality protocols and waste processing standards, pose negligible risks to human, animal, environmental and crop receptors, providing that risk management controls set within the standards and protocols are adhered to. Graphical abstract: Unlabelled Image Highlights: Quality assured, source-segregated composts and digestates have agronomic benefits. Removal of these wastes from regulation requires prior risk assessment. Risks to humans, animals, crops and the environment are negligible, assuming controls in place. Products from these wastes play an important role in a circular bioeconomy. The burden of proof to secure market confidence however is substantive.